Primary health care response to noncommunicable diseases: an assessment of Wellness Clinics in Ghana - Mawuli Komla Kushitor; Judith William; Deborah Esaa Larbi-Sarpong; Mary Akua Ampomah; Prince Owusu Adoma; Kennedy T. C. Brightson; Sandra Boatemaa Kushitor (BMC, 2024)
Abstract Background Globally, there is a significant unmet need for the rapidly growing burden of Non-Communicable Diseases (NCDs). Ghana has adopted and implemented Wellness Clinics (WC) nationwide to respond to the rising burden of NCDs. Regrettably, very little is known about WCs, including their structure and the services they offer. This study explores the concept of WC, their structure, position within the hospital environment, and services from the perspectives of healthcare providers and clients. Methods An exploratory qualitative study was conducted with health professionals (n = 12) and clients (n = 26) of Wellness Clinics in two district hospitals and one regional hospital in a deprived region of Ghana where NCDs are rising. Using the WHO-PEN approach, an interview guide was purposely designed for this study. The data were analysed thematically using Atlas.ti. Results All three Wellness Clinics were sub-units under the outpatient department. The WC was created by the facilities to respond to the increase in NCDs and to meet annual performance review requirements. The Wellness Clinics provided NCD diagnosis, counselling, and treatment services to approximately 300 clients per week at the facility level. Only one of the WCs provided NCD prevention services at the community level. Integrated NCD care was also provided at the WC, despite the health system and individual-level challenges reported by the health workers and clients. Conclusion The implementation of the Wellness Clinic demonstrates the government's commitment to addressing the increasing burden of NCDs in Ghana through the primary health system. To maximise the impact of the wellness clinics, we recommend developing best practices, providing logistics, and addressing health insurance challenges.